O Efeito da Supervisão Abusiva na Folga Orçamentária: O Papel Mediador da Exaustão Emocional e Moderador da Identidade Moral - Schmidt, Jefferson Leandro (2022)
This research aimed to analyze the effect of abusive supervision on budget slack with the mediating role of emotional exhaustion and moderator of moral identity, based on the epistemological basis of the Protection Motivation Theory (PMT), for the concreteness of responding to the problem that instigates this research. The present research is characterized as descriptive, survey type, quantitative approach and used statistical techniques and resources of analysis, through Structural Equation Models (ESM) and by the partial least square st regression method - Partial Least Squares (PLS), to analyze the effect of abusive supervision, mediated by emotional exhaustion and moderated by moral identity, on the budgetary gap of budget managers, agro-industrial cooperatives in the states of Paraná, Santa Catarina and Rio Grande do Sul. It is notepoint that the concern to know the factors that lead to the formation of budget slack, has led researchers to explore the origins and consequences for organizations, thus, it is justified to carry out this research to evidence the possibility of understanding the effects of behavioral factors of supervisors with their subordinates and the articulations with the budget. The participants of this research, 88 responsible for the preparation, execution and control of the budget of agro-industrial cooperatives participated. To measure the variables, we used questionnaires with a five-point Likert scale. The results indicate that for the sample used, hypothesis H1 was not confirmed, i.e., abusive supervision had no effect directly on budget slack. As for the H2 hypothesis, it can be confirmed, that is, it shows that emotional exhaustion measures the relationship between abusive supervision and budgetary slack. As for the H3 hypothesis, it cannot be confirmed, that is, moral identity, it did not moderate the relationship between emotional exhaustion and budgetary slack. It is concluded that the nonconfirmation of hypothesis H1 demonstrates a favorable work environment in agro-industrial cooperatives in Brazil, without abuse in the relations between supervisors and subordinates, and better allocation of resources, effectiveness and results. It is also concluded that subordinates suffering from abusive supervision, suffer from emotional exhaustion and to protect themselves or compensate, show the budgetary slack, and as much as they have a high moral identity, being in emotional exhaustion, will not take into account the moral issue. Regarding contributions, they cover questions: (i) theoretical, through the PMT lens, the inclusion of behavioral contexts such as Abusive Supervision and Emotional Exhaustion and its influence on Budget Slack; (ii) practices, analysis of the actions of individuals, in order to inhibit the budget gap, for a better allocation of resources; (iii) social, questions to reflect on the preparation of management positions and "supervisor-subordinate" relationships, for a conscious model for budgeting in a more harmonious environment. Thus, it allows reinforcing the need for analysis in the other branches of the cooperative sector, as well as other organizations.